Differences between Relative Energy Deficiency in Sport (RED-S) and Overtraining Syndrome in Endurance Athletes: A Systematic Review of Clinical, Endocrine and Performance-Based Indicators - Francuziak, Anna Ewelina; Dembicki, Piotr Mikołaj; Kozłowska, Kinga; Kalinowska, Weronika; Kulasza, Paulina Sara; Kaczmarek , Aleksandra; Kaczmarek , Wojciech; Bagiński, Konrad; Jabłonowska, Magdalena; Krakowiak, Magdalena (Quality in Sport, 2025)
Introduction: This review paper aims to systematically collate and compare published evidence on (1) clinical presentation, (2) endocrine/metabolic biomarkers, and (3) objective performance/physiological markers that differentiate RED-S from OTS in endurance athletes. Materials and Methods: A review of chosen literature in the PubMed database was conducted, using the following key words: , RED-S”, , OTS’’, , overtraining’’, , low energy availability’’, , athlete health’’ Summary: Relative Energy Deficiency in Sport (RED-S) and Overtraining Syndrome (OTS) are distinct clinical entities that frequently produce overlapping symptoms (fatigue, performance decline, mood disturbance), which complicates timely and correct diagnosis in endurance athletes. RED-S is driven primarily by low energy availability, whereas OTS arises from chronic imbalance between training load and recovery; both have different pathophysiological signatures and management implications. Recent consensus statements and growing biomarker research motivate a focused synthesis comparing the two syndromes. Conclusion: While RED-S and OTS represent distinct clinical entities, their overlapping features often lead to diagnostic challenges. Accurate differentiation is critical to ensuring athlete well-being, avoiding long-term adverse effects, and maximizing performance potential. Through systematic monitoring and individualized interventions, both conditions can be successfully managed, supporting athletes in achieving optimal training and competitive outcomes.